2015
DOI: 10.1681/asn.2014020210
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Myocyte-Derived Follistatin-Like 1 Prevents Renal Injury in a Subtotal Nephrectomy Model

Abstract: Heart disease contributes to the progression of CKD. Heart tissue produces a number of secreted proteins, also known as cardiokines, which participate in intercellular and intertissue communication. We recently reported that follistatin-like 1 (Fstl1) functions as a cardiokine with cardioprotective properties. Here, we investigated the role of cardiac Fstl1 in renal injury after subtotal nephrectomy. Cardiac-specific Fstl1-deficient (cFstl1-KO) mice and wild-type mice were subjected to subtotal (5/6) nephrecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 60 publications
0
47
1
Order By: Relevance
“…To investigate the effect of chronic kidney failure on host defense, we performed 5/6-nephrectomy in WT mice. This model system has been shown to reliably induce CKD in the murine system (20,21). Ten days after surgery, pneumonia was induced in these mice by intratracheal injection of viable E. coli bacteria (22).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the effect of chronic kidney failure on host defense, we performed 5/6-nephrectomy in WT mice. This model system has been shown to reliably induce CKD in the murine system (20,21). Ten days after surgery, pneumonia was induced in these mice by intratracheal injection of viable E. coli bacteria (22).…”
Section: Resultsmentioning
confidence: 99%
“…In agreement with this concept, the current study revealed no effect of either SPARC, SPARCL1 or MGE8 alone on (pro)renin synthesis by As4.1 cells. Additionally, ligands that are known to be involved in blood pressure regulation (NPPC, or natriuretic peptide precursor C), diabetic nephropathy (LGALS1 or galectin-1) 26 , nephrogenesis (MDK or midkine) 27 , renal fibrosis (WFDC2, or WAP four-disulfide core domain protein 2) 28 , and renal injury prevention (FSTL1, or follistatin-related protein 1) 29 also did not directly affect (pro)renin synthesis by As4.1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA from 500 ng of total RNA was synthesized by reverse transcription using ReverTra Ace qPCR RT master mix (Toyobo Life Science, Osaka, Japan) according to the manufacturer's instructions. Quantitative real-time RT-PCR analysis was performed on a CFX-96 system using Thunderbird qPCR mix (Toyobo Life Science) as a double-stranded DNA-specific dye according to the manufacturer's instructions (Bio-Rad, Hercules, CA) (20). Primers were designed as follows: 5=-ACCACCATCAAGGACTC-3= and 5=-TGACCACTCTCCCTTT G-3= for mouse TNF-␣, 5=-TTCCAATGCTCTCCTAACAG-3= and 5=-C TAGGTTTGCCGAGTAGATC-3= for mouse interleukin-6 (IL-6), 5=-AA ACGGTTTGTCTTCAAC-3= and 5=-ATGGTGAAGTCAATTATGTC-3= for mouse IL-1␤, 5=-CCACTCACCTGCTGCTACTCAT-3= and 5=-TGG TGATCCTCTTGTAGCTCTCC-3= for mouse MCP-1, 5=-TCCTTCTTG GGTATGGAATC-3= and 5=-TAGAGGTCTTTACGGATGTC-3= for mouse ␤-actin, 5=-TTGGGTCAGCACTGGCTCTG-3= and 5=-TGGCGG TGTGCAGTGCTATC-3= for mouse gp91 phox , 5=-CTGGCTGAGGCCAT CAGACT-3= and 5=-AGGCCACTGCAGAGTGCTTG-3= for mouse p67 phox , 5=-GATGTTCCCCATTGAGGCCG-3= and 5=-GTTTCAGGTC ATCAGGCCGC-3= for mouse p47 phox , 5=-TGGTGAACGTGGTGCCTA CA-3= and 5=-TGCAGTCACATCCCACCCT-3= for mouse CTRP9, 5=-C CAATCTGTGTCCTTCTAAC-3= and 5=-GTTTCTGAGCATCGTAGTT G-3= for rat TNF-␣, 5=-AAGGTCACTATGAGGTCTAC-3= and 5=-CAT ATTGCCAGTTCTTCGTA-3= for rat IL-6, and 5=-GGTCATCACTATCG GCAATG-3= and 5=-AGGTCTTTACGGATGTCAAC-3= for rat ␤-actin.…”
mentioning
confidence: 99%